Reye’s Syndrome: Diagnosed on a Postmortem Needle Liver Biopsy in an Unexplained Death - Moatasim, Ambreen; Haque, Anwar Ul; Rizwan, Humeira (International Journal of Pathology, 2018)
We report here a case of a 14 year old child whose disease remained undiagnosed till death, when the diagnosis of Reye’ssyndrome was established via a core needle biopsy of liver done for academic purposes. Although Reye’s syndrome is adiagnosis of exclusion, a high index of suspicion is critical for its diagnosis.